Avaliação do teste de micronúcleo em linfócitos para uso como biomarcador de risco de câncer em usuários de esteroides anabolizantes androgênicos - Souza, Leonardo da Cunha Menezes (2013)
The use of anabolic androgenic steroids (AAS) has grown among practitioners of recreational bodybuilding, with significant contributions of "Designer Steroids" (DS), EAA designed aiming muscle hypertrophy in healthy subjects. The abusive use of AAS in general is associated with adverse effects, one of the most worrisome is cancer development. Given that cancer is a genetic disease resulting from changes in genes critical in maintaining genomic stability and in the control of proliferation and differentiation, biomarkers able to identify these changes can take predictive value and contribute to reducing the high rates of morbidity and mortality by this disease. The aim of this study was to evaluate the effectiveness of the Cytokinesis Block Micronucleus Test (CBMN) in human lymphocytes in identifying risk groups for cancer development in users of AAS. Was collected 5ml of blood from 15 AAS users bodybuilders (G1), 20 nonusers bodybuilders (G2) and 20 nonusers sedentary (G3). Lymphocytes were cultured with blocking of cytokinesis and subsequent processing for making slides. MN analysis was performed on a minimum of 1000 binucleated lymphocytes. The occurrence of MN was significantly higher (p <0.05) in individuals of G1 compared to G2 and G3. The results indicate the sensitivity of CBMN in human lymphocytes in the identification of chromosomal damage in consequence of AAS using, however, further studies are needed to determine their potential to predict the cancer risk in users of AAS.